Död ved i vatten - funktionella strukturer och dess påverkan på öring (Salmo trutta, L.) - Bondesson, Anton (2014)
The background to this work was to see if there was a connection between large woody debris (LWD) and the presence of brown trout in our Swedish forest streams. Previous researches by Degerman et al. (2004) have shown that there is a strong correlation between the amount of dead wood and the presence of brown trout. The goal was then to find a way to restore, maintain and increase the trout habitats by constructing and adding manmade wooden structures that would mimic natural deadwood and its features in flowing water. The inspiration was partially taken from a water restoration program in the Klamath River of northern California, USA. The purpose with the wooden structures was to create spawning- and resting locations for the trout but also to attract insects which is the staple food for brown trout and to change the current to make the stream habitats more dynamic. The fieldwork took place in a part of Hedströmmen called Kyrkströmmen which is a regulated stream section connecting the lakes of Övre - and Nedre Vättern. This stream is located in the middle of Skinnskatteberg in the province of Västmanland, Sweden. To be able to see any change in the trout population over time and in practice we conducted electrofishing in two areas of the stream in the late spring of 2013. The first electrofishing was conducted without any LWD and the second time with the added wooden constructions. The results that were revealed in this study were not satisfying, at least not in the short run. In contrast, later implemented electrofishing revealed a more positive presence of brown trout in the area that housed a larger amount of dead wood. The conclusion is thus that there is a correlation between the amount of dead wood and the density of brown trout but the need for more research and fieldwork is needed.